Profile of the management of pharmaceutical products and medical consumables at primary healthcare centres in North Toraja district - Impa, Elson; Nita, Yunita; Priyandani, Yuni (Pharmacy Education, 2023)
Background: The management of pharmaceutical products and medical consumables in primary healthcare centres (PHCs)should be efficient, effective, and rational. Management is one of the competencies of pharmacists. Objective: This study aimed to describe the management profile of pharmaceutical products and medical consumables at primary healthcare centres in the North Toraja district. Method: This cross-sectional study used a questionnaire to collect data. The indicator for managing pharmaceutical products and medical consumables was based on technical guidelines for pharmaceutical service standards at primary healthcare centres issued by the Ministry of Health of the Republic of Indonesia in 2019. Research variables were planning, procurement, receipt, storage, distribution, disposal and recall, control, and administration. The sample consisted of all 28 PHCs in the North Toraja district. Results: The results from 27 PHCs showed that the management of pharmaceutical products and medical consumables consisted of planning (72.62%), procurement (66.06%), receipt (83.07%), storage (61.47%), distribution (66.69%), disposal and recall (33.84%), control (56.74%), and administration (62.36%). Conclusion: Managing pharmaceutical products and medical consumables at PHCs in the North Toraja district did not fully comply with pharmaceutical service standards.